Sustainable financing, climate change risks and bank stability in Kenya - Maureen Odongo; Roseline Nyakerario Misati; Caren Kageha; Peter Simiyu Wamalwa (Kenya Bankers Association (KBA), 2023)
This study analyses the impact of climate risk indicators on bank stability in Kenya based on descriptive and quantitative approaches on quarterly data covering thirtyfive banks over the period 2009 to 2021. The analysis reveals a distinct warming trend, variable rainfall pattern and an increasing trend in greenhouse gas emissions especially in the agriculture and transport sectors. Banks' climate financing for sustainable projects remains low. Empirical findings using dynamic panel estimation reveals adverse impact of temperature changes and rainfall variability on bank stability and credit risk arising from non-performing loans. The stress testing results reveal vulnerability of the banking sector to climate change as the probability of defaulting increases in moderate, severe, and extreme temperature changes. The results affirm banks' important role in managing financial stability risks while providing sustainable climate financing and the need to strengthen synergies between private and public sustainable financing for target priority sectors.
Keywords: 330